2009
DOI: 10.1016/j.neuroimage.2009.03.044
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence for the selective subcortical degeneration in Huntington's disease

Abstract: Although Huntington's disease is largely considered to be a subcortical disease, there is no clear consensus on whether all deep grey matter loss is a direct downstream consequence of the massive degeneration of the medium-size spiny neurons in the striatum. Our aim was to characterise in vivo such preferential degeneration by analysing various distinct diffusion imaging measures including mean diffusivity, anisotropy, fibre orientation (using the information of the principal diffusion direction) and white mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(157 citation statements)
references
References 48 publications
12
144
1
Order By: Relevance
“…Manual segmentation of the images using commercially available software was sufficient to extract volume measurements and achieve accuracy for large structures. By 12 weeks, volume loss was detectable in subcortical regions consistent with stereological and voxel-based morphometry studies (Kremer et al, 1990;Stack et al, 2005;Douaud et al, 2009).…”
Section: Decreases In Brain Volume Reflected Lack Of Growth and Degensupporting
confidence: 78%
“…Manual segmentation of the images using commercially available software was sufficient to extract volume measurements and achieve accuracy for large structures. By 12 weeks, volume loss was detectable in subcortical regions consistent with stereological and voxel-based morphometry studies (Kremer et al, 1990;Stack et al, 2005;Douaud et al, 2009).…”
Section: Decreases In Brain Volume Reflected Lack Of Growth and Degensupporting
confidence: 78%
“…Nevertheless, although these studies were valuable, they provided only a limited assessment of the CST because they used a whole brain or region of interest approach, with limited DTI parameters. Interestingly, an earlier DTI study showed a selective degeneration in the subcortical gray matter which lead to an increase in FA because of the hypothesized increased orientation of the fibers (Douaud et al 2009). Although our analysis of the CST also showed degeneration, our FA result was in the opposite direction, which emphasizes the importance of caution when interpreting diffusion data (Jones et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Diffusivity is an indirect marker of white matter tract organization. Increases of diffusivity across both the whole brain and in select white matter pathways, such as within the sensorimotor network, are suggestive of white matter degeneration in premanifest (preHD) and early manifest HD (Della Nave et al, 2010; Douaud et al, 2009; Dumas et al, 2012; Klöppel et al, 2008; Matsui et al, 2014; Novak et al, 2014; Odish et al, 2015; Poudel et al, 2014, 2015). In a recent study of the sensorimotor network, we observed a broad structural HD phenotype that encompassed gray and white matter volume, cortical thickness, and altered diffusivity in left white matter tracts in the sensorimotor network, which was associated with CAG repeat length (Orth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%